ISOTOPIC CRITERIA FOR THE ORIGIN OF MEYMECHITE MAGMATISM - Kogarko L.N.; Karpenko S.F.; Lyalikov A.V.; Teptelev M.P. (My University, 1988)
The authors studied the SM-Nd and Rb-Sr isotope systems in meymechite and picrite from the Maymecha-Kotuy alkalic province at the north margin of the Siberian craton. Meymechite and picrite here form numerous dikes and lava fields at the southwest margin of the Guli ultramafic alkalic pluton. Meymechite and picrite samples unaffected by secondary alteration were collected and studied. First, they were treated for 12 to 15 hr with 4N HCl at 110° to 115°C, and the insoluble residue was decomposed in a HF+HCl mixture. The resulting solutions were analyzed separately. It was thereby assumed that separate 'mineral phases' of these rock samples would be selectively dissolved and, therefore, that the internal isochron could be plotted. Study results are discussed.